Loneliness From the Perspectives of Elderly People: A Phenomenological Study - Majideh Heravi Karimloo; Monireh Anoosheh; Mahshid Foroughan; Mohammad Taghi Sheykhi; Ebrahim Hajizade; Monir Sadat Seyed Bagher Maddah; Isa Mohammadi; Fazlollah Ahmadi (University of Social Welfare & Rehabilitation Sciences, 2008)
Objectives: The purpose of this study was to explore the perspectives of elderly people on loneliness. Methods & Materials: Hermeneutic interpretive phenomenology was selected as the research methodology, and a sample of thirteen elders undertook in-depth interview. Participants were asked for descriptions of their day-to-day lived experiences of loneliness. The data were analyzed using van Mannen's thematic analysis. Results: The text revealed three common themes: feelings of pain and suffering, losses and deprivation and, compensation mechanisms. Conclusion: This study provides explicit knowledge about how older persons experience the phenomenon of loneliness. The lived experience of the older adults showed that loneliness is a feeling of pain and suffering which is related to the losses. Relationship with God, starting new relationships and reminiscences of the past were stressed as ways of coping or dealing with the loneliness experience. These findings can help the healthcare providers to define the sense of loneliness, the factors contributing to, and the mechanisms used by the adults to cope with it and perhaps the ways which may prevent it.